PENGARUH METODE DRILL PADA RENANG GAYA DADA UNTUK PESERTA DIDIK TUNA WICARA DI SEKOLAH LUAR BIASA DHARMA ASIH KOTA PONTIANAK - Yanda, Ryska April; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem that happened in this research is the lack of chest pool style learning method for the learners of speech in SLB Dharma Asih Pontianak . This study aims to determine the influence of drill methods on swimming style for learners of speech in SLB Dharma Asih Pontianak City. The form of research used is pre-experimental design this use one-group pretest-posttest desig n. The data collection tool is an assessment sheet with the number of 5 tests submitted. The sample of this research is the students of speech class VII, VIII and IX of SMP SLB B Dharma Asih of Pontianak City which amounted to 15 specially selected / nonrandom learners by using purposive sampling technique. Technique of data collection is done by using assessment sheet. Data analysis techniques by performing some tests with the help of SPPS Version 22. Based on data analysis result obtained pretest average equal to 61,3% and posttest equal to 74,7% with increase of 13,4 % . Then the result of T-test sig.0,00 3 <0,05 indicating that Ho rejected and Ha accepted meaning it can be concluded that there are differences in their the influence of drill methods on chest pool for learner SLB Dharma Asih Pontianak teaching students before and after being given treatment .Keywords : Drill Method, Pool Chest Style , Speech